Natural Area Weeds: A Property Owner's Guide to Melaleuca Control - Kenneth A. Langeland; M. J. Meisenburg (EDIS, 2005)
This publication is one of a series with the purpose of providing information to empower citizens of Florida to protect Florida's natural areas from melaleuca and other invasive plant species. This document is SS-AGR-96, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date October 2005.